2009
DOI: 10.1021/ja809656k
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of mRNA in Live Cells Using Nucleic Acid-Templated Reduction of Azidorhodamine Probes

Abstract: Nucleic acid-templated reactions leading to a fluorescent product represent an attractive strategy for the detection and imaging of cellular nucleic acids. Herein we report the use of a Staudinger reaction to promote the reduction of profluorescent azidorhodamine. The use of two cell-permeable GPNA probes, one labeled with the profluorescent azidorhodamine and the other with trialkylphosphine, enabled the detection of the mRNA encoding O-6-methylguanine-DNA methyltransferase in intact cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 41 publications
3
113
0
4
Order By: Relevance
“…16 These features had led us to explore PNA-GPNA hybrids as a platform in templated reactions and we had shown that probes as short as 6 mer provided sufficient duplex stability to promote a Staudinger reaction. 4,13 Our previous design used a rhodamine dye quenched by a single azide which provided a greater than 30 fold enhancement of fluorescence upon Staudinger reduction. To further enhance signal to noise ratio as well as sensitivity of the system, we explored a bis-azidorhodamine as shown in Fig.…”
Section: General Design Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 These features had led us to explore PNA-GPNA hybrids as a platform in templated reactions and we had shown that probes as short as 6 mer provided sufficient duplex stability to promote a Staudinger reaction. 4,13 Our previous design used a rhodamine dye quenched by a single azide which provided a greater than 30 fold enhancement of fluorescence upon Staudinger reduction. To further enhance signal to noise ratio as well as sensitivity of the system, we explored a bis-azidorhodamine as shown in Fig.…”
Section: General Design Principlesmentioning
confidence: 99%
“…PBS alone upon PNA-Azide treatment was used as a negative control (1). A cell permeable phosphine (tmTCEP) was used as a positive control to define the maximum fluorescence (4). Cells treated with the perfect match phosphine (PNA-phosphine-PM) show increased fluorescence intensity (3) compared to cells treated with the mismatched probe (PNA-phosphine-MM, 2).…”
Section: Mir-21 Quantification For Cells In Solutionmentioning
confidence: 99%
“…8). We first applied this strategy to coumarin (azidocoumarin [76] ) and then rhodamine (azidorhodamine, [77] bisazidorhodamine [78] ). In parallel, this strategy has been used by other research groups and applied to azidomethyl-fluorescein, [79] azidorhodamine, [80] bis-azidomethyl-fluorescein, [81] and bis-azidonaphtho-rhodamine.…”
Section: Te Mplated Reactionmentioning
confidence: 99%
“…This enabled the detection of mRNA in live cells using the azidorhodamine fluorophore. [77] A similar strategy using a bis-azidorhodamine bestowed with higher fluorescence performance (a 120 turn-on ratio vs. the 32-fold turn-on ratio of azido-rhodamine) was used to image and quantify miRNA across different cell lines using both fluorescence microscopy and flow cytometry (Fig. 9).…”
Section: Te Mplated Reactionmentioning
confidence: 99%
“…Another common strategy uses an oligonucleotide template to catalyze the formation of a fluorescent dye from two non‐ or weakly fluorescent precursors 4c, 6. Some of the reactions most commonly used in such applications include ester hydrolyses,7 nucleophilic substitutions,4a, 8 aldolizations,6 tetrazine ligations,5j,5k and the Staudinger reaction 5e,5i…”
mentioning
confidence: 99%